Musculoskeletal loading in the symptomatic and asymptomatic knees of middle‐aged osteoarthritis patients. Issue 2 (4th May 2016) - Sritharan, Prasanna; Lin, Yi‐Chung; Richardson, Sara E.; Crossley, Kay M.; Birmingham, Trevor B.; Pandy, Marcus G.
ABSTRACT: This study quantified the contributions by muscles, gravity, and inertia to the tibiofemoral compartment forces in the symptomatic (SYM) and asymptomatic (ASYM) limbs of varus mal‐aligned medial knee osteoarthritis (OA) patients, and compared the results with healthy controls (CON). Muscle forces and tibiofemoral compartment loads were calculated using gait data from 39 OA patients and 15 controls aged 49 ± 7 years. Patients exhibited lower knee flexion angle, higher hip abduction, and knee adduction angles, lower internal knee flexion torque but higher external knee adduction moment. Muscle forces were highest in CON except hamstrings, which was highest in SYM. ASYM muscle forces were lowest for biceps femoris short head and gastrocnemius but otherwise intermediate between SYM and CON. In all subjects, vasti, hamstrings, gastrocnemius, soleus, gluteus medius, gluteus maximus, and gravity were the largest contributors to medial compartment force (MCF). Inertial contributions were negligible. Highest MCF was found in SYM throughout stance. Small increases in contributions from hamstrings, gluteus maximus, gastrocnemius, and gravity at the first peak; soleus and rectus femoris at the second peak; and soleus, gluteus maximus, gluteus medius, and gravity during mid‐stance summed to produce significantly higher total MCF. Compared to CON, the ASYM limb exhibited similar peak MCF but higher mid‐stance MCF. In patients, diminished non‐knee‐spanning muscle forces did not produce correspondingly diminished MCF contributions due to the influence of mal‐alignment. Our findings emphasize consideration of muscle function, lower‐limb alignment, and mid‐stance loads in developing interventions for OA, and inclusion of the asymptomatic limb in clinical assessments. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:321–330, 2017.